Symptom Experience and Quality of Life of Patients with Breast Cancer Receiving Chemotherapy in Bangladesh (Bangladesh Journal of Medical Science, 2016)
Background: The present study was aimed to the relationships between symptom severity and distress and quality of life (QoL) of patients receiving chemotherapy for breast cancer.Objectives and methodology: A total number of 132 patients, attending both In-patient and Out-patient department and fulfilling the recruitment criteria were included in the study. A self-report questionnaire was used to collect data from the eligible participants by the primary investigator. The data were analyzed by using descriptive and inferential statistical tools. Results: On average, the participants of the study experienced seventeen symptoms with moderate level. The level of QoL of the participants was at moderate level (M=2.02, SD=0.39). Among all the subscales, the physical well-being had the lowest score and social well-being had highest score. Symptom experience and quality of life showed significant negative correlation. Conclusion: The patients with breast cancer would experience high symptoms during a 7-day period after receiving chemotherapy of the previous cycle. Nurses need to perform full measurement of multiple symptoms when care for breast cancer patients after the administration of chemotherapy.Bangladesh Journal of Medical Science Vol.15(2) 2016 p.201-206